PENGARUH KETERAMPILAN KERJA, KOMPENSASI DAN DISIPLIN KERJA TERHADAP KINERJA PERAWAT (STUDI KASUS RUMAH SAKIT ISLAM SULTAN AGUNG SEMARANG BAGIAN RAWAT INAP UNIT UMUM) - Asih Nor Istikomah; Wahyu Hidayat; Widayanto Widayanto (Universitas Diponegoro, 2014)
This study aims to determine the effect of job skills, compensation and work discipline on the performance of nurses. The population of this research is warn nurse in public unit section at Sultan Agung Islamic Hospital Semarang and researchers took a sample of 122 nurses. In linear regression analysis was used and the significance test using SPSS 20.0. From the data analysis it can be concluded that in partial, job skills has a positive effect on the performance of 26,6%, the compensationvariable has a positive influence on the performance behavior of 15,3%, and work discipline variable has positive effect on behavioral performance of 12,2%. Simultaneously job skills, compensation, and work discipline variable has a positive effect on the performance by 31,9%. Based on the research results, the researchers suggest that hospitals improve nursing skills in making decisions relating to nursing task followed by giving them profession allowance according to their expectation and educational status, and the relation with the discipline of work is the starting time, so the performances of the nurse can be increased optimally.